2017
DOI: 10.1155/2017/9160515
|View full text |Cite
|
Sign up to set email alerts
|

Neural Plasticity Associated with Hippocampal PKA-CREB and NMDA Signaling Is Involved in the Antidepressant Effect of Repeated Low Dose of Yueju Pill on Chronic Mouse Model of Learned Helplessness

Abstract: Yueju pill is a traditional Chinese medicine formulated to treat syndromes of mood disorders. Here, we investigated the therapeutic effect of repeated low dose of Yueju in the animal model mimicking clinical long-term depression condition and the role of neural plasticity associated with PKA- (protein kinase A-) CREB (cAMP response element binding protein) and NMDA (N-methyl-D-aspartate) signaling. We showed that a single low dose of Yueju demonstrated antidepressant effects in tests of tail suspension, forced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 45 publications
3
20
0
Order By: Relevance
“…Therefore, in this study, we explored the underlying mechanism of the stimulatory effect of MEM on tau phosphorylation by examining the expression of different NMDARs. Our results showed that CRS caused an increase in the levels of NMDARs containing GluN2A and GluN2B, which is in accordance with the previous studies [86], while MEM treatment suppressed the expression of both the GluN2A and GluN2B NMDAR subunits after 16-day CRS. In contrast, treatment with 5 mg/kg MEM did not suppress GluN2B upregulation following 28-day CRS and treatment with 10 mg/kg MEM even induced the upregulation of GluN2B expression compared to that in CRS-only mice.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, in this study, we explored the underlying mechanism of the stimulatory effect of MEM on tau phosphorylation by examining the expression of different NMDARs. Our results showed that CRS caused an increase in the levels of NMDARs containing GluN2A and GluN2B, which is in accordance with the previous studies [86], while MEM treatment suppressed the expression of both the GluN2A and GluN2B NMDAR subunits after 16-day CRS. In contrast, treatment with 5 mg/kg MEM did not suppress GluN2B upregulation following 28-day CRS and treatment with 10 mg/kg MEM even induced the upregulation of GluN2B expression compared to that in CRS-only mice.…”
Section: Discussionsupporting
confidence: 93%
“…It is, however, worth noting that the dose of CLM to induce rapid and lasting antidepressant effects was only half of the clinical dose. In contrast, higher than clinical dose was required for Yueju pill to elicit rapid antidepressant-like effects [19], whereas we found a single full clinical dose of Yueju only induced a shorter duration of antidepressant activity [27]. Importantly, we determined experimentally an optimal dose of CLM for rapid antidepressant-like response, which is consistent with the two half doses of prescription of the herb preparation for daily use in humans.…”
Section: Discussionsupporting
confidence: 62%
“…Further, crocin significantly increases the expression of p-CREB, brain-derived neurotrophic factor (BDNF), and vascular endothelial growth factor (VEGF) in the rat hippocampus [ 13 ]. Our previous research showed that Yueju pills [ 14 ] and gardenia [ 15 ] have antidepressant effects, with gardenia yellow pigment (GYP, a collection of compounds with shared structure of crocin) being one of the constituents responsible for their antidepressant efficacy [ 16 ]. Transcriptomic analyses detected a unique upregulation of hippocampal PACAP expression post Yueju (unpublished).…”
Section: Introductionmentioning
confidence: 99%